PERENCANAAN DESAIN BUNDARAN KAWASAN KAMPUS UNIVERSITAS JEMBER - Saad, Muhammad; Hayati, Nunung Nuring; Sulistyono, Sonya (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Two intersections in the campus of the University of Jember need attention. That name is Doubleway intersection and Triumviraat roundabout. This is related to the frequent occurrence of accidents at the intersection. Previous research conducted by Isnanto (2007) and Novel (2013) at  the Doubleway intersection. This intersection assumed into a roundabout, and the performance of the roundabout until 2023 showed DS ≤ 0.75. This study was conducted to evaluate the design of Doubleway and Triumviraat roundabout at the University of Jember. Evaluation results used to re-design of  Doubleway and Triumviraat roundabout in order to satisfy applicable standards/guidelines. So the safety aspect of the review of infrastructure can be realized. The diameters size results obtained from the design of the Doubleway and Triumviraat roundabout  is 38.5 m and 44.7 m. Performance of the each other roundabout  in 2014 showed  the DS value ≤ 0.75.